The State and Working Women : A Comparative Study of Britain and Sweden - Ruggie, Mary (Book collections on Project MUSE., 2014)
Mary Ruggie's controversial study of British and Swedish labor market, anti-discrimination, and child care programs argues that gender-based policy alone cannot substantially raise the economic status of women workers. Rather, policies for women must be developed within the context of more general economic and social policies Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preser.